2020
DOI: 10.1038/s41434-020-0172-6
|View full text |Cite|
|
Sign up to set email alerts
|

Maximizing lentiviral vector gene transfer in the CNS

Abstract: Gene transfer is a widely developed technique for studying and treating genetic diseases. However, the development of therapeutic strategies is challenging, due to the cellular and functional complexity of the central nervous system (CNS), its large size and restricted access. We explored two parameters for improving gene transfer efficacy and capacity for the selective targeting of subpopulations of cells with lentiviral vectors (LVs). We first developed a second-generation LV specifically targeting astrocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…79 These viral envelopes do not necessarily warrant specific cell-type tropism, and in most cases they are combined with cell-type-specific promoters to instigate transgene expression in the desired cell type. [81][82][83] Lentiviral vectors can deliver 8 kb of sequence, and that means they can accommodate larger transgenes than AAV vectors. 26 Lentiviral vectors have the advantages of highefficiency infection of dividing and non-dividing cells, longterm stable expression of a transgene, and low immunogenicity.…”
Section: Review Biomaterials Sciencementioning
confidence: 99%
“…79 These viral envelopes do not necessarily warrant specific cell-type tropism, and in most cases they are combined with cell-type-specific promoters to instigate transgene expression in the desired cell type. [81][82][83] Lentiviral vectors can deliver 8 kb of sequence, and that means they can accommodate larger transgenes than AAV vectors. 26 Lentiviral vectors have the advantages of highefficiency infection of dividing and non-dividing cells, longterm stable expression of a transgene, and low immunogenicity.…”
Section: Review Biomaterials Sciencementioning
confidence: 99%
“…The prominent role of astrocytic PGC-1a in regulating postnatal astrocyte development and synapse formation was confirmed in vivo by re-expressing PGC-1a in developing astrocytes on P5. The amGluR5cKO and control tdTomato mice were injected with an astrocyte-specific Lentivirus expressing PGC-1a or GFP or DsRed (Figures S7A and S7B; Petrelli et al, 2020;Humbel et al, 2021). RT-PCR analysis showed that the injection of Lenti:PGC-1a into the PFC of am-GluR5cKO-tdTomato mice significantly increased PGC1a mRNA levels (Figure S7C).…”
Section: Re-expression Of Pgc-1a In Mglur5-deficient Astrocytes Restores Astrocyte Morphogenesis and Synaptogenesismentioning
confidence: 99%
“…Notably, lentiviruses pseudotyped with glycoproteins from the lymphocytic choriomeningitis virus, the Moloney murine leukemia virus [229], the Mokola virus [230,231], or the chikungunya virus [232] were reported to acquire tropism towards astrocytes. As discussed in the context of AAV development, the use of an astrocyte-specific promoter is also valuable to achieve cell-specific gene transfer, mainly with the addition of a miRNA de-targeting strategy to abolish residual transgene expression in neuronal cells [230,233,234].…”
Section: Viral Deliverymentioning
confidence: 99%